Sensory retraining improves light touch threshold of the paretic hand in chronic stroke survivors: a single-subject A-B design. (2nd April 2020) - Hejazi-Shirmard, Mahnaz; Taghizadeh, Ghorban; Azad, Akram; Lajevardi, Laleh; Rassafiani, Mehdi
Abstract: Background: Light touch, one of the primary and basic sensations, is often neglected in sensory retraining programmes for stroke survivors. Objective: This study aimed to investigate the effects of sensory retraining on the light touch threshold of the hand, dexterity and upper limb motor function of chronic stroke survivors. Methods: Five chronic stroke survivors with sensory impairment participated in this single-subject A-B design study. In baseline (A) phase, they only received standard rehabilitation. In the treatment (B) phase, they received a 6-week sensory retraining intervention in addition to standard rehabilitation. In both phases, they were evaluated every 3 days. Light touch threshold, manual dexterity and upper limb motor function were assessed using Semmes-Weinstein Monofilaments, Box-Block Test and Fugl-Meyer Assessment, respectively. Visual analysis, nonparametric Mann-Whitney U test and, c-statistic were used for assessing the changes between phases. Results: All participants indicated changes in trend or slope of the total score of light touch or both between the two phases. The results of the c-statistic also showed the statistical difference in the total score of light touch between baseline and treatment in all participants ( p < 0.001). Also, the results of the c-statistic and Mann-Whitney U test supported the difference of manual dexterity and motor function of the upper limb between baseline and treatment in all participants ( p < 0.001). Conclusion: Current findings showed that sensory retraining may be an effective adjunctive intervention for improving the light touch threshold of the hand, dexterity and upper limb motor function in chronic stroke survivors.